Carbon aerogel for wastewater purification-water photolysis hydrogen production and preparation method thereof

By designing carbon aerogel materials for solar power, combining Cu-MOF/SA porous carbon aerogels and loaded Au nanoparticles and ZnIn2S4 catalysts, efficient purification of wastewater and photocatalytic hydrogen production are achieved, which solves the problems of freshwater shortage and water pollution in the prior art, and reduces the cost of hydrogen production and improves efficiency.

CN119608051APending Publication Date: 2025-03-14TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311664098.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-06
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing solar-powered water hydrogen production system mainly uses pure water, which leads to shortage of fresh water and water pollution problems. The complex gas-solid two-phase reaction system increases the cost and difficulty.

Method used

Carbon aerogel is used as a dual-functional material for interfacial photothermal wastewater purification and photocatalytic hydrolysis to produce hydrogen. Through the design of Cu-MOF/SA porous carbon aerogel and supported Au nanoparticles and ZnIn2S4 catalyst, efficient purification of wastewater and photocatalytic hydrogen production are achieved.

Benefits of technology

The cost of photolysis hydrogen production catalyst is reduced, its activity and stability is improved, and continuous hydrogen production with low carbon emissions, low cost and high efficiency is achieved. It also effectively utilizes wastewater, promoting the large-scale production of hydrogen energy and the resource utilization of wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608051A_ABST
    Figure CN119608051A_ABST
Patent Text Reader

Abstract

The invention provides carbon aerogel for wastewater purification and hydrogen production through water photolysis and a preparation method of the carbon aerogel, Au / Cu-MOF / SA carbon aerogel serves as a photothermal evaporation module to be used for interface photothermal wastewater purification driven by solar energy, and ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel serves as a photocatalytic reaction module to be used for photocatalytic hydrolysis hydrogen production. By designing the composite carbon aerogel, solar energy is positioned on a gas-liquid interface for evaporation of wastewater; and then the purified distilled water is used as a raw material for hydrogen production through photocatalytic hydrolysis, so that integration of wastewater purification and hydrogen production through water photolysis is realized. The upper photo-thermal layer and the photocatalytic layer are exposed on the water surface due to the self-floating characteristic of the system, so that efficient light transmission can be realized, light attenuation caused by water can be reduced to the greatest extent, and the problem that a traditional powder photocatalyst is difficult to recycle can be effectively solved; hydrogen can be stably generated for a long time in waste water containing various pollutants, and great commercial application potential is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of energy science and catalytic technology, and specifically relates to a carbon aerogel for a solar-driven interfacial photothermal wastewater purification-photocatalytic hydrolysis hydrogen production system and a preparation method thereof. Background Art

[0002] Solar-driven water hydrogen production is considered to be an extremely promising hydrogen production technology solution for achieving a sustainable carbon-neutral economy, and is increasingly recognized by academia and industry. However, most of the current solar-driven water hydrogen production systems use pure water as raw material to produce hydrogen, and the increasing shortage of fresh water and water pollution have greatly limited their practical applications. If wastewater can be linked to hydrogen production, it will perfectly solve energy and environmental problems.

[0003] Based on this, researchers have proposed two technical solutions: direct photolysis of wastewater to produce hydrogen and photolysis of water to produce hydrogen after wastewater purification. The former is to directly use wastewater for photocatalytic water decomposition to produce hydrogen, but this technology is not mature. The complex water quality components of wastewater will cause serious blockage and corrosion to the photocatalyst, and the efficiency of photocatalytic water decomposition to produce hydrogen is low; the latter indirect hydrogen production is mainly through a front steam generator to convert liquid wastewater into gaseous water, and transport it to the photocatalytic module for gas-solid two-phase photocatalytic hydrogen production reaction. In theory, the gas-solid two-phase reaction system can avoid direct corrosion of the catalyst and provide a high-purity substrate for the photocatalytic reaction. In addition, the gas-solid two-phase reaction interface is conducive to the desorption of the reaction products, which increases the efficiency of photocatalytic hydrogen production. However, the complex reaction system and inefficient steam generation capacity greatly increase the cost, manufacturing difficulty and operation and maintenance costs of the system. Therefore, it is of great significance to develop a method that can utilize renewable energy to purify wastewater and carry out gas-solid two-phase photocatalytic hydrogen production reaction in a timely manner, while effectively isolating the contact between the liquid environment and the catalytic reaction sites and inhibiting the influence of the adverse reaction environment on the catalytic performance. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a carbon aerogel and its preparation method for a solar-driven interfacial photothermal wastewater purification-photocatalytic hydrolysis hydrogen production system in view of the deficiencies of the above-mentioned prior art. The solar-driven interfacial photothermal wastewater purification-photocatalytic hydrolysis hydrogen production system is mainly divided into two parts: one is a photothermal evaporator for wastewater purification, and the other is a photocatalytic reactor using the purified water for photocatalytic hydrogen production. Specifically, under light conditions, the self-floating carbon aerogel can position solar energy at the air-water interface, which is beneficial to prevent heat loss and enhance heat localization; the ordered water channels of the Cu-MOF / SA porous carbon aerogel can enhance the long-distance vertical rapid transport of water to support high-rate steam generation on the evaporation surface; the Au nanoparticles loaded on its surface are excited by photons to produce a plasmon effect, accelerating the transformation of liquid phase water into gas phase water; at the same time, the purified water is transported to the photocatalytic reactor, and the surface of the carbon aerogel in the photocatalytic reactor is loaded with a semiconductor photocatalyst ZnIn2S4 with high catalytic activity, and photocatalytic hydrogen production is carried out when light irradiates its surface. This system reduces the cost of photocatalytic hydrogen production from water splitting while improving its activity and stability, and can achieve low-carbon emissions, low-cost, and high-efficiency continuous hydrogen production.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing carbon aerogel for wastewater purification-photolysis of water to produce hydrogen, the method comprising the following steps:

[0006] S1. Preparation of Cu-MOF porous framework materials:

[0007] The copper nitrate trihydrate aqueous solution was added dropwise to the dimethylimidazole aqueous solution, and the reaction was stirred at room temperature. After the reaction was completed, the product was centrifuged, washed with distilled water, and then vacuum dried to obtain a Cu-MOF porous framework material;

[0008] S2. Preparation of Cu-MOF / SA aerogel:

[0009] The Cu-MOF porous framework material obtained in S1 is made into a Cu-MOF aqueous solution, and then sodium alginate is added, stirred evenly, poured into a customized mold, and directionally frozen with liquid nitrogen, and then freeze-dried to obtain a Cu-MOF / SA aerogel; the Cu-MOF / SA aerogel is added to a calcium chloride aqueous solution for a cross-linking reaction, washed with distilled water after the reaction, and freeze-dried again to obtain a cross-linked Cu-MOF / SA aerogel;

[0010] S3. Preparation of Cu-MOF / SA carbon aerogel:

[0011] The cross-linked Cu-MOF / SA aerogel obtained in S2 is placed in a tubular furnace for calcination and carbonization under a N2 atmosphere to obtain a Cu-MOF / SA carbon aerogel;

[0012] S4. Preparation of PVP-modified gold nanoparticle methanol solution:

[0013] The sodium citrate aqueous solution is added to the boiling chloroauric acid aqueous solution, and stirred to obtain a gold nanoparticle hydrosol; the PVP aqueous solution is added to the gold nanoparticle hydrosol, and stirred to react to obtain a PVP-modified gold nanoparticle hydrosol; the PVP-modified gold nanoparticle hydrosol is centrifuged, washed with anhydrous methanol, and finally dispersed in anhydrous methanol to obtain a PVP-modified gold nanoparticle methanol solution;

[0014] S5. Preparation of Au / Cu-MOF / SA carbon aerogel:

[0015] The PVP-modified gold nanoparticle methanol solution obtained in S4 is loaded onto the top of the Cu-MOF / SA carbon aerogel obtained in S3 by physical deposition, and after the aerogel is completely absorbed, it is vacuum dried to obtain Au / Cu-MOF / SA carbon aerogel;

[0016] Preparation of S6 and ZnIn2S4 powder photocatalysts:

[0017] Dispersing ZnCl2, InCl3 and thioacetamide in ethylene glycol in sequence to form a mixed solution, then placing the mixed solution in a reactor for a synthesis reaction, cooling to room temperature after the reaction, centrifuging, washing the precipitated material with deionized water and anhydrous ethanol respectively, and then vacuum drying to obtain a ZnIn2S4 powder photocatalyst;

[0018] S7. Preparation of ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel:

[0019] The ZnIn2S4 powder photocatalyst obtained by S6 was uniformly dispersed in anhydrous ethanol to obtain a ZnIn2S4 ethanol solution; the ZnIn2S4 ethanol solution was then loaded on the surface of the Au / Cu-MOF / SA carbon aerogel by physical deposition, and after the aerogel was completely absorbed, it was vacuum dried to obtain the ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel.

[0020] Preferably, the molar ratio of copper nitrate trihydrate to dimethylimidazole in S1 is 1:1, the concentration of the copper nitrate trihydrate aqueous solution is 0.1-0.2 mol / L, and the concentration of the dimethylimidazole aqueous solution is 0.1-0.2 mol / L;

[0021] Preferably, the stirring reaction time in S1 is 3 to 5 hours; the vacuum drying temperature is 60° C. and the time is 12 hours.

[0022] Preferably, the mass fraction of Cu-MOF in the Cu-MOF aqueous solution in S2 is 0.1-0.3wt%, the mass fraction of sodium alginate is 1-3wt%; the customized mold is polytetrafluoroethylene iron Teflon brass; the mass fraction of the calcium chloride aqueous solution is 3-5wt%;

[0023] Preferably, the cross-linking reaction time in S2 is 3 to 5 hours; the freeze-drying temperature is -40°C and the time is 24 to 48 hours.

[0024] Preferably, the calcination conditions in S3 are: heating to 350°C at a rate of 2°C / min, keeping warm for 1 hour, then heating to 700°C at a rate of 5°C / min, keeping warm for 2 hours, and then cooling naturally.

[0025] Preferably, the mass fraction of the sodium citrate aqueous solution in S4 is 1-2wt%; the mass fraction of the chloroauric acid aqueous solution is 0.005-0.01wt%; the volume ratio of the sodium citrate aqueous solution to the chloroauric acid aqueous solution is 7:1000; the stirring time after the sodium citrate aqueous solution is added to the chloroauric acid aqueous solution is 10-20min;

[0026] Preferably, the mass fraction of the PVP aqueous solution in S4 is 2-3wt%, and it is prepared with polyvinyl pyrrolidone PVP-K30, and the relative molecular mass of PVP-K30 is 40000; the volume ratio of the gold nanoparticle hydrosol to the PVP aqueous solution is 50:1; the stirring time of the PVP aqueous solution after adding the gold nanoparticle hydrosol is 20-28h; the centrifugal speed is 11000rpm, and the time is 5min;

[0027] Preferably, the concentration of the methanol solution of PVP-modified gold nanoparticles finally obtained in S4 is 0.0003-0.0012 mol / L.

[0028] Preferably, the vacuum drying in S5 is carried out at a temperature of 60° C. and for a period of 12 h.

[0029] Preferably, the molar ratio of ZnCl2, InCl3 and thioacetamide in S6 is 1:2:4; the temperature of the synthesis reaction is 120-180°C, and the time is 12-24h; the temperature of the vacuum drying is 60-80°C, and the time is 8-12h.

[0030] Preferably, the concentration of the ZnIn2S4 ethanol solution in S7 is 1-7 g / L; the temperature of the vacuum drying is 60°C and the time is 12 h.

[0031] The present invention also provides the application of the carbon aerogel prepared by the above method, wherein the carbon aerogel is Au / Cu-MOF / SA and ZnIn2S4 / Au / Cu-MOF / SA composite carbon aerogel, which is used for solar-driven interfacial photothermal wastewater purification-photocatalytic hydrolysis hydrogen production integration. Among them, Au / Cu-MOF / SA carbon aerogel is used as a photothermal evaporation module for solar-driven interfacial photothermal wastewater purification, and ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel is used as a photocatalytic reaction module for photocatalytic hydrolysis hydrogen production.

[0032] The performance test method of Au / Cu-MOF / SA carbon aerogel for interfacial photothermal water evaporation is as follows: Au / Cu-MOF / SA carbon aerogel is placed in a device containing a certain amount of water. A xenon lamp with an AM 1.5G filter is used as the light source to simulate the intensity of 1 sun (1kW·m -2 ) was irradiated above the device to perform interfacial photothermal water evaporation. In the experiment, the surface temperature of Au / Cu-MOF / SA carbon aerogel was monitored with an infrared thermal imager, and the water evaporation performance was reflected by monitoring the mass loss of the solution using an electronic balance. The mass of water was recorded every 5 minutes to calculate the water evaporation rate. Water evaporation tests were also carried out in different water sources to detect the changes in ion concentrations in the original solution and the collected distilled water to reflect its wastewater purification capacity.

[0033] The performance test method of ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel for photocatalytic hydrolysis and hydrogen production is as follows: ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel is placed in a photocatalytic reactor filled with different water sources, and the entire reactor is sealed by snap-locking. A xenon lamp with an AM 1.5G filter is used as the light source, and photocatalytic activity is carried out under irradiation above the device. Through the automatic sampling device of the test system, the product gas is passed into the gas chromatograph for hydrogen production calibration. The gas chromatograph is equipped with a thermal conductivity detector (TCD) and high-purity argon (99.999%) as a carrier gas. The hydrogen production is calculated based on the retention time and the peak area calibrated with standard H2 gas.

[0034] The experimental method for using Au / Cu-MOF / SA and ZnIn2S4 / Au / Cu-MOF / SA composite carbon aerogels for solar-driven interfacial photothermal wastewater purification-photocatalytic water splitting to produce hydrogen is as follows: the Au / Cu-MOF / SA carbon aerogel is placed in a container containing pure water or wastewater to be evaporated which is arranged in the middle of the photothermal evaporator; a water inlet is provided on the side of the photothermal evaporator for injecting wastewater into the container; a water outlet is provided on the lower side for the evaporated wastewater to enter the photocatalytic reactor through the water outlet after cooling, thereby ensuring the continuity of interfacial photothermal wastewater purification-photocatalytic water splitting to produce hydrogen. The water outlet of the photothermal evaporator and the water inlet of the photocatalytic reactor are connected with a U-shaped tube to prevent the gas in the photocatalytic reactor from flowing back to the photothermal evaporator; the ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel is put into the photocatalytic reactor filled with purified distilled water; an opening is provided on the other side of the photocatalytic reactor for connecting a water removal device and a gas storage device to collect hydrogen; the top is sealed with a quartz glass plate, and high-purity nitrogen or argon is used as a carrier gas to carry the hydrogen generated by catalysis out of the reactor. Using sunlight or a xenon lamp with an AM 1.5G filter as the light source, Au / Cu-MOF / SA carbon aerogel loaded with Au nanoparticles produces photothermal effect and capillary action to vaporize and cool the sewage, and then transports it to the photocatalytic reactor through a connecting vessel. ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel loaded with ZnIn2S4 catalyst and Au nanoparticles is excited by light, produces photothermal effect, capillary action and carriers, converts liquid water into gaseous water, and then photocatalytically decomposes it into hydrogen. The wastewater purification ability of carbon aerogel is investigated by comparing the water quality conditions before and after different wastewater treatments, and its functional application is realized. Specifically, it can be used to purify organic dyes, heavy metal ions, etc. in wastewater driven by solar energy.

[0035] Compared with the prior art, the present invention has the following advantages:

[0036] 1. The present invention provides a carbon aerogel for a solar-driven interfacial photothermal wastewater purification-photocatalytic hydrolysis hydrogen production system and a preparation method thereof. The system uses sunlight as a light source to achieve integrated wastewater purification and photocatalytic hydrolysis hydrogen production, while reducing carbon emissions and solving the problem of wastewater being difficult to discharge. Wastewater is used to prepare hydrogen, which is expected to promote the large-scale production of hydrogen energy and the resource utilization of wastewater. The preparation process of the Au / Cu-MOF / SA and ZnIn2S4 / Au / Cu-MOF / SA composite carbon aerogels of the present invention is relatively simple, low-cost, and mature in process, and is suitable for large-scale production; at the same time, the method of use is simple, and it only needs to be put into wastewater, and then it can be used under natural light irradiation at room temperature and pressure, and it has the advantages of being easy to recycle and not causing secondary pollution.

[0037] 2. The present invention utilizes Cu-MOF / SA carbon aerogel with rich pore structure and high specific surface area as the matrix for water transport, and loads precious metal Au nanoparticles with plasma primitive effect and / or semiconductor catalytic material ZnIn2S4 with photocatalytic activity thereon, so that it has the dual functions of efficient interfacial photothermal water evaporation and photocatalytic hydrolysis to produce hydrogen. The present invention adopts a directional freezing process to form a directional pore structure inside the aerogel when preparing the Cu-MOF / SA carbon aerogel substrate material to enhance its specific surface area and porosity, which is beneficial for the carbon aerogel to quickly adsorb water vapor. MOF can be deposited on the aerogel pore wall with the directional growth of ice crystals, which is beneficial for the full exposure of MOF particles and the maximum utilization of pores, thereby accelerating photothermal evaporation and photocatalytic reactions.

[0038] 3. The Au / Cu-MOF / SA carbon aerogel self-floating photothermal module loaded with Au nanoparticles designed by the present invention can locate solar energy at the air-water interface, improve the photothermal conversion performance of the photothermal module, and use carbonized substrate materials to further enhance the absorption of sunlight and increase the rate of water vapor generation.

[0039] 4. The self-floating photocatalytic ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel loaded with ZnIn2S4 catalyst and Au nanoparticles designed by the present invention is based on a gas-solid two-phase photocatalytic reaction, which can not only reduce the adsorption barrier of water molecules on the catalyst surface, but also reduce the diffusion resistance of the product hydrogen, improve the hydrogen escape and collection efficiency, thereby significantly improving the photocatalytic hydrogen production rate. In addition, under the synergistic effect of solar light and heat, it breaks the limitation of the semiconductor band gap structure in the photocatalytic hydrolysis hydrogen production process, and promotes water vaporization in the form of heat with the low-energy infrared light that usually cannot be absorbed and utilized, and assists in promoting the photocatalytic hydrogen production process.

[0040] The present invention is further described in detail below with reference to the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 It is a scanning electron microscope image of the Au / Cu-MOF / SA carbon aerogel prepared in Example 1 of the present invention.

[0042] Figure 2 This is a transmission electron micrograph of the ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel prepared in Example 1 of the present invention.

[0043] Figure 3 It is the interface photothermal water evaporation rate of different evaporation systems under one sunlight intensity in Example 5 of the present invention.

[0044] Figure 4It is the rate of hydrogen production by photocatalytic water decomposition of different catalytic systems under one sunlight intensity in Example 6 of the present invention.

[0045] Figure 5 It is a schematic diagram of the integrated test device for interfacial photothermal wastewater purification and photolysis of water to produce hydrogen used in Example 7 of the present invention. DETAILED DESCRIPTION

[0046] Example 1

[0047] This embodiment is a method for preparing a carbon aerogel for a solar-driven interfacial photothermal wastewater purification-photocatalytic hydrolysis hydrogen production system, the method comprising the following steps:

[0048] S1. Preparation of Cu-MOF porous framework materials:

[0049] Prepare 0.2 mol / L copper nitrate trihydrate aqueous solution and 0.2 mol / L dimethylimidazole aqueous solution respectively; slowly add the copper nitrate trihydrate aqueous solution to the dimethylimidazole aqueous solution under stirring at room temperature, continue to stir and react for 4 hours after the addition is completed, and after the reaction is completed, centrifuge the product (speed is 1000 rpm, time is 5 min), wash with distilled water for 3 times, and then vacuum dry at 60°C for 12 hours to obtain a Cu-MOF porous framework material.

[0050] S2. Preparation of Cu-MOF / SA aerogel:

[0051] Weigh 0.03g Cu-MOF powder and disperse it in 30mL deionized water, ultrasonically treat it for 10min to obtain a suspension; then, slowly add 0.9g SA powder to the above suspension under continuous magnetic stirring, stir for 5h, pour the obtained uniform solution into a customized polytetrafluoroethylene iron Teflon brass mold, and let it stand for 2h to defoam. Then put the customized mold into liquid nitrogen for directional freezing for 10min, and finally freeze-dry it at below -40℃ for 48h to obtain Cu-MOF / SA aerogel; put the Cu-MOF / SA aerogel into a 5wt% calcium chloride aqueous solution for crosslinking for 4h, and then wash it with deionized water to remove excess Ca 2+ , and freeze-dried again for 24 h to obtain the cross-linked Cu-MOF / SA aerogel.

[0052] S3. Preparation of Cu-MOF / SA carbon aerogel:

[0053] The cross-linked Cu-MOF / SA aerogel was placed in a corundum crucible and carbonized in a tubular furnace under a N2 atmosphere. The temperature was increased to 350°C at a rate of 2°C / min. After being kept warm for 1 hour, the temperature was increased to 700°C at a rate of 5°C / min. After being kept warm for 2 hours, the aerogel was naturally cooled to obtain Cu-MOF / SA carbon aerogel.

[0054] S4. Preparation of PVP-modified gold nanoparticle methanol solution:

[0055] 0.1 g of sodium citrate was dissolved in 10 mL of deionized water to obtain a sodium citrate aqueous solution; 255 mg of polyvinyl pyrrolidone (PVP-K30) was dissolved in 10 mL of deionized water to obtain a PVP aqueous solution; 10 mg of chloroauric acid trihydrate was dissolved in 100 mL of deionized water, heated to boiling under stirring, and then 0.7 mL of sodium citrate aqueous solution was quickly added thereto, and stirring was continued for 15 min to obtain a gold nanoparticle aqueous sol; 2 mL of the PVP aqueous solution was added to 100 mL of the gold nanoparticle aqueous sol, and stirring was continued for 24 h to obtain a PVP-modified gold nanoparticle aqueous sol; 30 mL of the PVP-modified gold nanoparticle aqueous sol was centrifuged (speed of 11000 rpm, time of 5 min) and washed with anhydrous methanol, and finally dispersed in 10 mL of anhydrous methanol to obtain a PVP-modified gold nanoparticle methanol solution with a concentration of 0.0009 mol / L.

[0056] S5. Preparation of Au / Cu-MOF / SA carbon aerogel:

[0057] 10 mL of the PVP-modified gold nanoparticle methanol solution obtained by S4 was used to spray the gold nanoparticles onto the top of the Cu-MOF / SA carbon aerogel by an electric spray gun. After the carbon aerogel was completely absorbed, it was dried at 60 °C for 12 h to obtain the Au / Cu-MOF / SA carbon aerogel for the photothermal module, which was called Au / Cu / CSA-9.

[0058] Preparation of S6 and ZnIn2S4 powder photocatalysts:

[0059] 1mmol ZnCl2, 2mmol InCl3 and 4mmol thioacetamide (TAA) were dispersed in 35mL ethylene glycol and ultrasonically treated for 10-30min. Then, the mixed solution was transferred to a Teflon-lined stainless steel high-pressure tank, heated at 180℃ for 12h, cooled to room temperature, centrifuged (speed 1000rpm, time 5min), and the precipitate was washed with deionized water and anhydrous ethanol respectively. Finally, the collected sample was dried under vacuum at 60℃ for 10h to obtain ZnIn2S4 powder photocatalyst.

[0060] S7. Preparation of ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel:

[0061] 50 mg of ZnIn2S4 powder photocatalyst obtained by S6 was uniformly dispersed in 10 mL of anhydrous ethanol and ultrasonically treated for 20 min to obtain a ZnIn2S4 ethanol solution with a concentration of 5 g / L. The solution was atomized and sprayed on the surface of the Au / Cu-MOF / SA carbon aerogel obtained by S5 using an electric spray gun. After the aerogel was completely absorbed, it was dried at 60 ° C for 12 h to obtain a photocatalytic module ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel, called ZIS / Au / Cu / CSA-50.

[0062] Figure 1 This is a scanning electron microscope image (×10 μm) of the Au / Cu-MOF / SA carbon aerogel prepared in this embodiment. It can be seen from the figure that the material adopts a directional freezing process to form a tightly packed unidirectional multi-porous structure inside the carbon aerogel, which is conducive to the carbon aerogel to use capillary action to quickly transport water and diffuse steam.

[0063] Figure 2 This is a transmission electron micrograph (×100 nm) of the ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel prepared in this embodiment. It can be seen from the figure that ZnIn2S4 and gold nanoparticles are evenly distributed on the surface of the material, which is beneficial to positioning solar energy at the air-water interface.

[0064] Example 2

[0065] The differences between this embodiment and embodiment 1 are that (1) the concentration of the methanol solution of PVP-modified gold nanoparticles in S4 is 0.0012 mol / L, and the obtained Au / Cu-MOF / SA carbon aerogel is called Au / Cu / CSA-12; (2) the concentration of the ethanol solution of ZnIn2S4 in S7 is 7 g / L, and the obtained ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel is called ZIS / Au / Cu / CSA-70; the other methods and steps are the same as those in embodiment 1.

[0066] Example 3

[0067] The difference between this embodiment and embodiment 1 is that (1) the concentration of the methanol solution of PVP-modified gold nanoparticles in S4 is 0.0006 mol / L, and the obtained Au / Cu-MOF / SA carbon aerogel is called Au / Cu / CSA-6; (2) the concentration of the ethanol solution of ZnIn2S4 in S7 is 3 g / L, and the obtained ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel is called ZIS / Au / Cu / CSA-30; other methods and steps are the same as those in embodiment 1.

[0068] Example 4

[0069] The difference between this embodiment and embodiment 1 is that (1) the concentration of the methanol solution of PVP-modified gold nanoparticles in S4 is 0.0003 mol / L, and the obtained Au / Cu-MOF / SA carbon aerogel is called Au / Cu / CSA-3; (2) the concentration of the ethanol solution of ZnIn2S4 in S7 is 1 g / L, and the obtained ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel is called ZIS / Au / Cu / CSA-10; other methods and steps are the same as those in embodiment 1.

[0070] Example 5

[0071] This embodiment is a performance test of Au / Cu-MOF / SA carbon aerogel for interfacial photothermal water evaporation, including the following steps:

[0072] The Au / Cu-MOF / SA carbon aerogels with different deposition amounts and a diameter of 3 cm were placed in a device filled with 50 mL of deionized water. A xenon lamp with an AM 1.5G filter was used as the light source to simulate the 1-sun light intensity (1 kW·m -2 ) irradiated Au / Cu-MOF / SA carbon aerogel above the device for 1 hour to perform interfacial photothermal water evaporation. In the experiment, the surface temperature of Au / Cu-MOF / SA carbon aerogel was monitored by an infrared thermal imager, and the water evaporation performance was reflected by monitoring the mass loss of the solution using an electronic balance, and the mass of water was recorded every 5 minutes; then the water evaporation rate of Au / Cu-MOF / SA carbon aerogel with different deposition amounts was calculated. Finally, the Au / Cu-MOF / SA carbon aerogel with the best performance was tested for water evaporation in different water sources, and the changes in ion concentrations in the original solution and the collected distilled water were detected to obtain data.

[0073] Figure 3 The results of the experiments were compared between deionized water, Cu-MOF / SA carbon aerogel and Au / Cu-MOF / SA carbon aerogel at 1 kW·m -2The mass change of water in the device under the illumination condition of . The results show that within the 1h irradiation time, the evaporation rate of pure water is the lowest, and the evaporation rate of the Au / Cu-MOF / SA carbon aerogel is the highest. This is because the upper and lower layers of the Au / Cu-MOF / SA carbon aerogel both promote the evaporation of water. Due to the porous and hydrophilic properties of the lower layer of Cu-MOF / SA carbon aerogel, the water body can be quickly transported to the locally heated upper surface of the Cu-MOF / SA carbon aerogel through capillary action, and its self-floating and low thermal conductivity properties can position solar energy at the gas-liquid interface, so that the Au nanoparticles in the upper layer can fully absorb sunlight, generate heat by plasmon effect, and the generated heat energy only heats the water transported to the upper surface, thereby improving the water evaporation efficiency and reducing heat loss. Therefore, within the same time, the Au / Cu-MOF / SA carbon aerogel has the best evaporation efficiency. In addition, compared with the evaporation rate of Cu-MOF / SA carbon aerogel, the evaporation rate of Au / Cu-MOF / SA carbon aerogel loaded with Au nanoparticles increased significantly under the same irradiation time, further demonstrating that the introduction of Au nanoparticles can effectively improve the photothermal conversion performance of the material and is beneficial to water evaporation. Figure 3 The effects of Au / Cu-MOF / SA carbon aerogels with different Au nanoparticle deposition amounts on the interfacial photothermal water evaporation performance were also compared. The results showed that the interfacial photothermal water evaporation rates of Au / Cu / CSA-3, Au / Cu / CSA-6, Au / Cu / CSA-9 and Au / Cu / CSA-12 were 1.09 kg·m -2 ·h -1 , 1.21kg·m -2 ·h -1 , 1.43kg·m -2 ·h -1 and 1.39 kg·m -2 ·h -1, the Au / Cu / CSA-9 sample of Example 1 has better interfacial photothermal water evaporation performance than other samples. It shows that the amount of Au nanoparticles introduced has a certain influence on the performance of the composite material. When the amount of gold nanoparticles introduced is small, the photothermal conversion capacity of the material is small; when the amount of gold nanoparticles introduced is large, the gold nanoparticles will be agglomerated together, resulting in a decrease in the photothermal conversion capacity of the material. This is because the introduction of Au nanoparticles blocks the water passage on the carbon aerogel to a certain extent, which reduces the number and volume of the surface voids of the carbon aerogel. Therefore, even if a higher temperature is reached, the evaporation amount is reduced due to insufficient water. In the present invention, the concentration and amount of sodium citrate have a great influence on the synthesis of gold nanoparticles, and the properties of gold nanoparticles of different sizes are also different. The volume ratio of chloroauric acid solution to sodium citrate solution, and the mass ratio of solute to solvent when configuring the two solutions are all for obtaining gold nanoparticles of a specific size range. The size of the gold nanoparticles prepared by the present invention is concentrated between 30 and 50 nm. Its small size causes it to have a high surface energy, so it is easy to agglomerate. By modifying PVP on the surface of gold nanoparticles, the agglomeration of gold nanoparticles during storage and synthesis of composite materials can be effectively avoided.

[0074] The Au / Cu / CSA-9 of Example 1 was used for solar-driven interfacial photothermal purification of wastewater. The carbon aerogel can -1 The original solution of heavy metal ions (Fe 3+ , Cu 2+ 、Co 2+ 、Zn 2+ etc.) or 0.2mg·L -1 It still has a high evaporation efficiency in organic dye wastewater (methyl orange, methylene blue, etc.) or real coal mine wastewater. By comparing the test stock solution and the collected distilled water, it is found that the removal rates of the three are all around 95%, showing great potential in purifying wastewater with a variety of pollutants.

[0075] Example 6

[0076] This example is a performance test of ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel for photocatalytic hydrolysis to produce hydrogen, including the following steps:

[0077] The ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel was placed in a photocatalytic reactor filled with 50 mL of different water sources, and the entire reactor was sealed by snap-locking. A xenon lamp with an AM 1.5G filter was used as the light source to simulate the 1-sun light intensity (1 kW·m -2) was irradiated from above the device for photocatalytic activity. The product gas was introduced into a gas chromatograph through the automatic sampling device of the test system for hydrogen production calibration. The gas chromatograph was equipped with a thermal conductivity detector (TCD) and high-purity argon (99.999%) as a carrier gas. The hydrogen production was calculated based on the retention time and the peak area calibrated with standard H2 gas.

[0078] ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel has a good hydrogen production rate. This is because, under sunlight irradiation, Cu-MOF / SA carbon aerogel can quickly transport liquid water to the surface of Cu-MOF / SA carbon aerogel due to its hydrophilicity and capillary action, and use the Au nanoparticles and ZnIn2S4 catalyst loaded on the surface to trigger the photo-thermal synergistic catalytic decomposition of water vapor to produce hydrogen at the gas-solid interface, thereby realizing solar-driven efficient interfacial photothermal water vaporization catalytic decomposition to produce hydrogen. The synergistic effect of solar light and heat in ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel breaks the limitation of the semiconductor band gap structure in the process of photocatalytic hydrolysis to produce hydrogen, and promotes water vaporization in the form of heat in the low-energy infrared light that is usually not absorbed and utilized, and assists in promoting the photocatalytic hydrogen production process. In addition, the floating property of the carbon aerogel exposes the upper photocatalytic layer above the water surface, which can not only achieve efficient light transmission, but also minimize the light attenuation caused by water, and effectively solve the problem that traditional powder catalysts are difficult to recycle and reuse.

[0079] Figure 4 The effects of different ZnIn2S4 deposition amounts on the photocatalytic hydrogen production performance of ZnIn2S4 / Au / Cu-MOF / SA carbon aerogels were compared. The results showed that the photocatalytic hydrogen production rates of ZIS / Au / Cu / CSA-10, ZIS / Au / Cu / CSA-30, ZIS / Au / Cu / CSA-50 and ZIS / Au / Cu / CSA-70 were 673 μmol·m -2 ·h -1 、1166μmol·m -2 ·h -1 、1451μmol·m -2 ·h -1 and 1409 μmol·m -2 ·h -1. From the overall trend, with the increase of ZnIn2S4 deposition amount, the roughness of the surface of the modified material gradually increases, which leads to increased diffuse reflection, enhanced absorption of light, and gradually increased water evaporation flux, resulting in hydrogen production from ZnIn2S4. However, when the deposition amount reaches 70 mg, the hydrogen production rate shows a downward trend. This is because too much ZnIn2S4 blocks the water passage to a certain extent, reduces the reabsorption of light in the pores, reduces the utilization rate of light energy, and limits the transport of water due to the reduction of capillary action, which reduces its evaporation and reduces the hydrogen production rate; it may also be because too much ZnIn2S4 covers the Au nanoparticles, so that it does not produce an effective photothermal conversion effect. Therefore, ZIS / Au / Cu / CSA-50 has the best photocatalytic hydrogen production effect.

[0080] Example 7

[0081] This embodiment is a test of Au / Cu-MOF / SA and ZnIn2S4 / Au / Cu-MOF / SA composite carbon aerogels for solar-driven interfacial photothermal wastewater purification-photocatalytic water splitting hydrogen production integration, including the following steps:

[0082] Figure 5 It is a schematic diagram of the test device for the integration of interfacial photothermal wastewater purification and photocatalytic water splitting for hydrogen production. The device is mainly composed of a photothermal evaporator and a photocatalytic reactor. A container containing wastewater to be evaporated and purified is set in the middle of the photothermal evaporator; a water injection port is provided on the side of the photothermal evaporator for injecting wastewater into the container; a water outlet is provided on the lower side for the evaporated wastewater to enter the photocatalytic reactor through the water outlet after cooling, so as to ensure the continuity of interfacial photothermal wastewater purification and photocatalytic water splitting for hydrogen production. The water outlet of the photothermal evaporator and the water inlet of the photocatalytic reactor are connected with a U-shaped tube to prevent the gas in the photocatalytic reactor from flowing back to the photothermal evaporator. An opening is provided on the other side of the photocatalytic reactor for connecting the water removal device and the gas storage device to collect hydrogen.

[0083] Place the device outdoors in a sunny place or use a xenon lamp with an AM 1.5G filter as the light source, put Au / Cu / CSA-9 into the photothermal evaporator, and put ZIS / Au / Cu / CSA-50 into the photocatalytic reactor. Under real sunlight, water droplets in the photothermal evaporator can be clearly seen flowing down the inner wall of the container. After 6 hours of illumination experiment, use compressed nitrogen or argon with a flow control device as the carrier gas at 5-50mL·min -1 The reaction pool is purged at a flow rate of, and the tail gas passes through the water removal device and finally enters the gas collection device.

[0084] The Au / Cu-MOF / SA and ZnIn2S4 / Au / Cu-MOF / SA composite carbon aerogels prepared by the present invention can achieve a mass flow rate of 1.36 kg·m -2·h -1 The rate of evaporation was 647 μmol·m -2 ·h -1 In addition, the system can produce hydrogen at a rate of 100 mg·mL -1 The original solution of heavy metal ions (Fe 3+ , Cu 2+ 、Co 2+ 、Zn 2+ etc.) or 200 μg·mL -1 It can maintain more than 95% of its original performance in organic dye wastewater (methyl orange, methylene blue, etc.) or real coal mine wastewater.

[0085] The present invention uses Au / Cu-MOF / SA carbon aerogel with high photothermal conversion efficiency to purify wastewater, and then loads semiconductor photocatalyst on the carbon aerogel to obtain ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel as a photocatalytic reaction module to achieve continuous and efficient hydrogen production of wastewater; Au / Cu-MOF / SA and ZnIn2S4 / Au / Cu-MOF / SA composite carbon aerogels realize interfacial photothermal evaporation under sunlight, and after evaporation, fresh water enters the photocatalytic reactor through a connecting vessel as a hydrogen production raw material; the self-floating characteristics of the carbon aerogel loaded with semiconductor catalysts effectively isolate the contact between the liquid environment and the catalytic reaction site, and inhibit the influence of the adverse reaction environment on the catalytic performance; the carbon aerogel uses photothermal effect and capillary action to transport water to its surface for vaporization, and the catalyst material is excited under light to generate carriers to react with gaseous water for photocatalytic hydrogen production. This reaction system not only exhibits high catalytic hydrogen production performance in pure water, but also can produce hydrogen in sewage with multiple pollutants for a long time and stably, and has great commercial application potential. At the same time, its preparation process is relatively simple, low-cost, mature technology, and suitable for large-scale production.

[0086] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing carbon aerogel for wastewater purification-photolysis of water to produce hydrogen, characterized in that: The method comprises the following steps: S1. Preparation of Cu-MOF porous framework materials: The copper nitrate trihydrate aqueous solution was added dropwise to the dimethylimidazole aqueous solution, and the reaction was stirred at room temperature. After the reaction was completed, the product was centrifuged, washed with distilled water, and then vacuum dried to obtain a Cu-MOF porous framework material; S2. Preparation of Cu-MOF / SA aerogel: The Cu-MOF porous framework material obtained in S1 is made into a Cu-MOF aqueous solution, and then sodium alginate is added, stirred evenly, poured into a customized mold, and directionally frozen with liquid nitrogen, and then freeze-dried to obtain a Cu-MOF / SA aerogel; the Cu-MOF / SA aerogel is added to a calcium chloride aqueous solution for a cross-linking reaction, washed with distilled water after the reaction, and freeze-dried again to obtain a cross-linked Cu-MOF / SA aerogel; S3. Preparation of Cu-MOF / SA carbon aerogel: The cross-linked Cu-MOF / SA aerogel obtained in S2 is placed in a tubular furnace for calcination and carbonization under a N2 atmosphere to obtain a Cu-MOF / SA carbon aerogel; S4. Preparation of PVP-modified gold nanoparticle methanol solution: The sodium citrate aqueous solution is added to the boiling chloroauric acid aqueous solution, and stirred to obtain a gold nanoparticle hydrosol; the PVP aqueous solution is added to the gold nanoparticle hydrosol, and stirred to react to obtain a PVP-modified gold nanoparticle hydrosol; the PVP-modified gold nanoparticle hydrosol is centrifuged, washed with anhydrous methanol, and finally dispersed in anhydrous methanol to obtain a PVP-modified gold nanoparticle methanol solution; S5. Preparation of Au / Cu-MOF / SA carbon aerogel: The PVP-modified gold nanoparticle methanol solution obtained in S4 is loaded onto the top of the Cu-MOF / SA carbon aerogel obtained in S3 by physical deposition, and after the aerogel is completely absorbed, it is vacuum dried to obtain Au / Cu-MOF / SA carbon aerogel; Preparation of S6 and ZnIn2S4 powder photocatalysts: Dispersing ZnCl2, InCl3 and thioacetamide in ethylene glycol in sequence to form a mixed solution, then placing the mixed solution in a reactor for a synthesis reaction, cooling to room temperature after the reaction, centrifuging, washing the precipitated material with deionized water and anhydrous ethanol respectively, and then vacuum drying to obtain a ZnIn2S4 powder photocatalyst; S7. Preparation of ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel: The ZnIn2S4 powder photocatalyst obtained by S6 was uniformly dispersed in anhydrous ethanol to obtain a ZnIn2S4 ethanol solution; the ZnIn2S4 ethanol solution was then loaded on the surface of the Au / Cu-MOF / SA carbon aerogel by physical deposition, and after the aerogel was completely absorbed, it was vacuum dried to obtain the ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel.

2. The preparation method according to claim 1, characterized in that: S1 The molar ratio of copper nitrate trihydrate to dimethylimidazole is 1:1, the concentration of the copper nitrate trihydrate aqueous solution is 0.1-0.2 mol / L, and the concentration of the dimethylimidazole aqueous solution is 0.1-0.2 mol / L; the stirring reaction time is 3-5 h; the vacuum drying temperature is 60°C and the time is 12 h.

3. The preparation method according to claim 1, characterized in that: S2 The mass fraction of Cu-MOF in the Cu-MOF aqueous solution is 0.1-0.3wt%, and the mass fraction of sodium alginate is 1-3wt%; the customized mold is polytetrafluoroethylene iron Teflon brass; the mass fraction of the calcium chloride aqueous solution is 3-5wt%; the cross-linking reaction time is 3-5h; the freeze-drying temperature is -40°C, and the time is 24-48h.

4. The preparation method according to claim 1, characterized in that: The calcination conditions in S3 are: heating to 350°C at a rate of 2°C / min, keeping the temperature for 1 hour, then heating to 700°C at a rate of 5°C / min, keeping the temperature for 2 hours, and then cooling naturally.

5. The preparation method according to claim 1, characterized in that: S4: the mass fraction of the sodium citrate aqueous solution is 1-2wt%; the mass fraction of the chloroauric acid aqueous solution is 0.005-0.01wt%; the volume ratio of the sodium citrate aqueous solution to the chloroauric acid aqueous solution is 7:1000; the stirring time after the sodium citrate aqueous solution is added to the chloroauric acid aqueous solution is 10-20min; The mass fraction of the PVP aqueous solution is 2-3wt%, and it is prepared with polyvinyl pyrrolidone PVP-K30, and the relative molecular mass of PVP-K30 is 40000; the volume ratio of the gold nanoparticle hydrosol to the PVP aqueous solution is 50:1; the stirring time after the PVP aqueous solution is added with the gold nanoparticle hydrosol is 20-28h; The final concentration of the PVP-modified gold nanoparticle methanol solution is 0.0003-0.0012 mol / L.

6. The preparation method according to claim 1, characterized in that: The vacuum drying temperature in S5 is 60° C. and the time is 12 h.

7. The preparation method according to claim 1, characterized in that: S6 The molar ratio of ZnCl2, InCl3 and thioacetamide is 1:2:4; the temperature of the synthesis reaction is 120-180°C, and the time is 12-24h; the temperature of the vacuum drying is 60-80°C, and the time is 8-12h.

8. The preparation method according to claim 1, characterized in that: S7 The concentration of the ZnIn2S4 ethanol solution is 1-7 g / L; the temperature of the vacuum drying is 60°C and the time is 12 h.

9. An application of the carbon aerogel prepared by the method according to any one of claims 1 to 8, characterized in that: The carbon aerogel is Au / Cu-MOF / SA and ZnIn2S4 / Au / Cu-MOF / SA composite carbon aerogel, which is used in a solar-driven interfacial photothermal wastewater purification-photocatalytic hydrolysis hydrogen production system.

10. The use of the carbon aerogel according to claim 9, characterized in that: The Au / Cu-MOF / SA carbon aerogel is used as a photothermal evaporation module for solar-driven interfacial photothermal wastewater purification, and the ZnIn2S4 / Au / Cu-MOF / SA carbon aerogel is used as a photocatalytic reaction module for photocatalytic hydrolysis to produce hydrogen.

Citation Information

Cited By

  • Sewage degradation and photocatalytic hydrogen production coupling device

    CN120383365A